Avaliação geoecológica da produção de energia eólica onshore no litoral norte e sul de Sergipe - Santos, Paulo Henrique Neves (2022)
The global agendas around climate issues demand from humanity more attractive practices that minimize the impacts of human activities on the landscape. In this sense, the production of wind energy is highlighted as one of the most promising practices in the energy segment to meet sustainable agendas. However, the implementation of onshore wind farms in the coastal zone has been triggering socio-territorial problems, largely caused by the marginalization of the socio-territorial context, identified as one of the main impacts of this energy matrix. Given this, the present study seeks to evaluate the viability of onshore wind energy production on the coast of Sergipe through a geoecological approach, considering its natural properties and its socio-territorial context. For this, a methodological approach was adopted based on the precepts of the functionalist approach of the Geoecology of Landscapes, analyzing the geoenvironmental conditions for the production of onshore wind energy, classifying them from the SWOT matrix, in a cut of 5 km of distance from the coastline, both on the south coast and on the north coast of the state of Sergipe. Composed of Neogene and Quaternary morphologies, the morpho-sculpture of the north and south coast of Sergipe is marked by dynamism and instability, in general, fragile in the face of urban-industrial processes, where a complex socioterritorial mosaic is inserted, with a predominance of tourist activities. , second homes, shrimp production, and subsistence practices by traditional and quilombola communities. From the evaluations, it was evidenced that the Quaternary morphologies are not suitable for the implantation of wind farms, since they are intrinsically linked to the dynamics of the winds, where any artificial alteration of these dynamics can trigger processes of degradation of the fields of sandstone deposits, fundamental for the protection of the coast of Sergipe against scenarios of variation in the mean sea level. On the other hand, the Coastal Tablelands, when located at a distance of less than 5 km from the coastline, maybe the most suitable areas for the implementation of onshore wind energy on the north coast of Sergipe, since they present a relatively more morphosculpture stable than the Coastal Plain, have adequate road infrastructure and have a low potential for generating socio-territorial conflicts considering the current uses, developed in this space-time cut. In this sense, considering the adopted spatial cut, the morphosculptures of the Coastal Tablelands located on the north coast of Sergipe are the geoecologically most suitable areas for the production of onshore wind energy. Although its relief has a certain degree of roughness, the Tablelands have a more stable morpho-cultural structure than the Quaternary, have an incidence of winds similar to the Plains, and have relatively less potential for socio-territorial conflicts due to the current socio-economic dynamics.